Preventive Check-Ups: Between the Promise of Certainty and the Uncertainty of Future Outcomes - Granero, Mariano; Velazquez, Alberto (Revista del Hospital Italiano de Buenos Aires, 2026)
Uncertainty permeates medical practice, yet it is often concealed beneath promises of certainty and control. This article invites reflection on how physicians and patients relate to uncertainty, and how communication and the therapeutic relationship can become central tools of care when no clear answers are available. Written from and for primary care, it uses a clinical vignette to raise questions that may enrich everyday practice.